Determinación de técnica de caracterización radiométrica de radionúclidos artificiales en suelos aledaños a instalación de almacenamiento de desechos radiactivos para seguimiento ambiental (2022)
Throughout the monographic research presented in this work, it was sought to relate the different characterization techniques used for the identification of radionuclides in soil matrices available in Colombia, with the different factors such as economics, sample preparation, capacity of the technique, among others. In Bogotá, where the Centralized Facility for Radioactive Waste Management (ICGDR) of the Colombian Geological Service (SGC) is located. In order to establish the appropriate environmental and radiological technique for the follow-up carried out by the ICGDR.